Existence and nonexistence of solutions of reaction-diffusion equation with Robin boundary condition - Öztürk, E. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We investigate the long-time behavior of the reaction-diffusion equation, which has a nonlinearity of polynomial growth of any order, with Robin boundary condition. Sufficient conditions are obtained for the solutions of the problem to be bounded or approaching infinity at a finite time.